Neural networks with R : smart models using CNN, RNN, deep learning, and artificial intelligence principles /: smart models using CNN, RNN, deep learning, and artificial intelligence principles. (2017) - Ciaburro, Giuseppe; (Computer scientist), Venkateswaran, Balaji
No abstract available